(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2024)
From the current paradigm of literary education, the need to promote creativity at all educational stages is emphasized, as it significantly impacts the acquisition and development of literary competence, as well as the creation of a personal connection with literary texts, the discovery of aesthetic pleasure, and consequently, the development of human artistic sensitivity (Ballester, 2015). Building upon these premises, this study describes research conducted with a literary creation workshop as the focal point for the development of literary creativity, carried out in the Postgraduate Diploma of Specialization in Reading and Literary Education in the 21st century at the University of Valencia. The productions developed will be qualitatively analyzed, as well as the students’ evaluations regarding the workshop. The results obtained highlight the relevance of fostering literary writing and creativity in the formation of competent readers.